PENGARUH PEMBERIAN KOLKISIN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI HITAM (Glycine max (L.) merr) - Fathurrahman Fathurrahman (UIR Press, 2016)
The aims of this study was to determine the effect of colchicine on growth and yield the black soybean for cikurai varieties. This research was conducted at the experimental farm Faculty of Agriculture, Riau Islamic University. The experimental design used was completely randomized design (CRD) factorial of two factors. The first factor was the concentration of colchicine (K factor) which consists of 4 levels K0 (0%), K1 (0.01%), K2 (0.05%), K3 (0.1%). The second factor is the soaking time (factor P) which consists of 4 levels: P1 (3 hours), P2 (6 hours), P3 (12 hours) and P4 (18 hours). The results showed that the interaction of colchicine concentration and soaking on the parameters of the seed crop had a significant effect only on seeds weight with concentration of 0.1% and 18 hours for soaking (K3P4) and produced 30.87 g. on average. The highest yield was a single concentration and had significant difference on treatment K3 (0.1%) for all parameters, namely flowering age, plant height, seeds weight, and 100 seeds weight. While the soaking time treatment alone had a significant effect on flowering age and seed weight on P4 (18 hours).